Mastering Microsoft Exchange Server 2016 - Leonard, Clifton; Svidergol, Brian; Wright, Byron; Meloski, Vladimir (Sybex, a Wiley brand, 2016)
A bestselling Exchange Server guide, updated for the 2016 release Mastering Microsoft Exchange Server 2016 is the gold-standard reference for system administrators and first-time users alike. Fully updated to align with the latest release, this expert-led guide provides comprehensive coverage and easy-to-follow tutorials for all aspects of Exchange Server installation, configuration, and management. Whether you're migrating from an earlier version or installing Exchange Server for the first time, this book gives you quick access to the answers you need. Step-by-step instructions walk you through planning and design, installation, administration and management, maintenance, and more, so you can get up to speed quickly and get back to work. With a focus on the hands-on details, the Microsoft Certified Masters author team provides practical insight and invaluable guidance on every aspect of Exchange Server 2016, from mastering the basics to leveraging new features. Microsoft Exchange allows access to e-mail, voicemail, and calendars at any time, from almost any device. The 2016 release is designed specifically to appeal to enterprises; if you've been tasked with the implementation, this guide has the information you need.-Get up to speed with the latest changes and features -Understand server configurations, requirements, installation, and migration -Manage mailboxes, groups, connectivity, and the client access server -Troubleshoot common issues efficiently and effectively Exchange Server 2016 shifts even more control to the user, freeing administrators to perform more critical tasks. Beefed-up architecture and more centralized functions have eased configuration and upgrades, and a robust cloud implementation is expected to draw enterprises sooner rather than later. Systems administrators need to become familiar with the latest changes, and Mastering Microsoft Exchange Server 2016 is the ultimate reference and tutorial.